On "Sourcery," or Code as Fetish. - Hui Kyong Chun, Wendy (Configurations)
This essay offers a sympathetic interrogation of the move within new media studies toward "software studies." Arguing against theoretical conceptions of programming languages as the ultimate performative utterance, it contends that source code is never simply the source of any action; rather, source code is only source code after the fact: its effectiveness depends on a whole imagined network of machines and humans. This does not mean that source code does nothing, but rather that it serves as a kind of fetish, and that the notion of the user as super agent, buttressed by real-time computation, is the obverse, not the opposite of this "sourcery."